2018
DOI: 10.1002/jcsm.12304
|View full text |Cite
|
Sign up to set email alerts
|

Tracking disease progression non‐invasively in Duchenne and Becker muscular dystrophies

Abstract: BackgroundAnalysis of muscle biopsies allowed to characterize the pathophysiological changes of Duchenne and Becker muscular dystrophies (D/BMD) leading to the clinical phenotype. Muscle tissue is often investigated during interventional dose finding studies to show in situ proof of concept and pharmacodynamics effect of the tested drug. Less invasive readouts are needed to objectively monitor patients' health status, muscle quality, and response to treatment. The identification of serum biomarkers correlating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 49 publications
9
64
0
Order By: Relevance
“…A total of 30 proteins showed significant association with age. At least 21 of them were already known in the DMD field as proteins able to discriminate between DMD patients and heathy controls in other recent studies in patients' sera . Less evidence was available for the other nine proteins, namely, NES, BASP1, C4A, MAP 4, C4BPA, CFH, KRT10, RELB, and PDZK1.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 30 proteins showed significant association with age. At least 21 of them were already known in the DMD field as proteins able to discriminate between DMD patients and heathy controls in other recent studies in patients' sera . Less evidence was available for the other nine proteins, namely, NES, BASP1, C4A, MAP 4, C4BPA, CFH, KRT10, RELB, and PDZK1.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little information regarding changes in miRNAs abundances/expression over time. Previous studies used age as an indicator of disease progression and compare miRNA levels in patients of different ages (18). Also, the effects of corticoid treatment are most commonly accessed between the treated and untreated groups of patients.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, extensive proteomic, RNA and metabolite analyses have been carried out in animal models and patients, as discussed in a number of excellent reviews on potential biomarkers for muscle, blood and urine (Aartsma-Rus et al, 2018; Aartsma-Rus and Spitali, 2015;Dowling et al, 2019;Hathout et al, 2014Hathout et al, , 2016Lourbakos et al, 2017;Parolo et al, 2018;Szigyarto and Spitali, 2018;Thangarajh et al, 2019). A large-scale proteomic approach to identify serum biomarkers associated with pathophysiological change over time (Spitali et al, 2018) concluded that ∼33 proteins were bona fide biomarkers as they were able to discriminate between DMD patients and healthy controls in all cohorts, with a concordant directional change towards either a consistent increase or decrease in patients.…”
Section: Overview Of Molecular Biomarkers Especially For Myonecrosismentioning
confidence: 99%